Pengembangan Puzzle Kreatif Untuk Media Pembelajaran Anak Sekolah Dasar - Alzanah, Lulu; Dewi, Happy Indira (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
The background of the research is that there has not been developed learning media that attracts students’ interest and motivation to learn which has an impact on student learning outcomes which are still low. The type of research is research and development (R&D). The development model used is the ADDIE , which includes analysis, design, development, implementation, evaluation. This research develops learning media in the form of creative puzzles for elementary school children. The development of creative puzzle learning media for Pancasila material is carried out through the potential and problem stage, the data collection stage, the product design stage, the product validation and testing stage (small scale), the revision stage, and the product use stage in the classroom. Based on media and material experts, the creative puzzle learning media for Pancasila material is very suitable to be used as a learning medium by making revisions according to expert suggestions and comments. The percentage of eligibility given by media experts is 96.67% and material experts is 94.55%. Creative puzzle learning media for Pancasila material received positive responses from students and teachers, and was effective for use in improving thematic learning outcomes of the theme of my experience as indicated by an increase in the value of learning outcomes. The average learning outcomes before using creative puzzle learning media was 64.08 and after using creative puzzle learning media an average of 78.28 with an increase of 22.16%.